Factores de riesgo de anemia en lactantes de la institución prestadora de servicios de salud Rumococha Iquitos 2020 - Sifuentes García, Kristina Stefany (2022)
The objective was to determine the maternal and infant risk factors associated with Anemia in infants aged 2 to 12 months attended at the IPRESS I-1 Rumococha de Iquitos 2020. Quantitative method a non-experimental design, cases and controls. Population 40 mothers with children from 2 to 12 months. The techniques: interview and documentary analysis and instruments: maternal and child risk questionnaire (validity 90.4% and reliability 89.6%), questionnaire of knowledge about infant feeding (validity 89, 1% and reliability 84.6%) and registration form for anemia. It is concluded in maternal factors: significant statistical association between the presence of anemia with maternal age (p = 0.004; OR = 6.857); marital status (p = 0.010; OR = 6.000); degree of instruction (p= 0.000; OR = 13.222); family income (p= 0.000; OR = 17.000) parity (p = 0.002; OR = 9.000) and maternal knowledge about infant feeding (p = 0.002; OR = 4.500). No statistically significant association was found between anemia and maternal occupation (p = 0.057). In the infant factors: statistically significant association between anemia and age (p = 0.27; OR = 4.333); breastfeeding (p = 0.000; OR = 36.000); Malnutrition (p = 0.000; OR = 12.000); Pneumonia (p = 0.011; OR = 5.444) and Child Growth and Development Control (p = 0.000; OR = 13.222). No statistically significant association was found between anemia and sex (p = 0.113).